The genome sequence of an ichneumonid wasp, Gelis areator (Panzer, 1804) [version 1; peer review: 2 approved] - Gavin R. Broad; James McCulloch; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual female Gelis areator (ichneumonid wasp; Arthropoda; Insecta; Hymenoptera; Ichneumonidae). The genome sequence has a total length of 228.10 megabases. Most of the assembly (98.97%) is scaffolded into 12 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 25.02 kilobases in length.